Collective Loans among Women Weavers and Access to Formal Credit: An Exploratory Sequential Mixed-Method Study - Nurnazmi; Wisadirana, Darsono; Kholifah, Siti; Chawa, Anif Fatma (Journal of Cultural Analysis and Social Change, 2025)
Women weavers in Eastern Indonesia face serious barriers to accessing formal credit, despite their vital roles in sustaining household economies and preserving intangible cultural heritage. This study analyzes weavers’ experiences in accessing formal credit through collective loan schemes, interprets the meaning of fund use and repayment strategies in everyday life, and empirically tests the relationships among credit access, fund utilization patterns, repayment strategies, and household economic empowerment. An exploratory sequential mixed-method design was employed, beginning with interpretative phenomenology and followed by a survey of 326 respondents. The research instrument demonstrated high content validity (Aiken’s V = 0.79), adequate reliability (α = 0.719; ω = 0.729), and strong construct validity via confirmatory factor analysis (factor loadings 0.498–0.660, excellent fit). The findings show that formal credit is perceived as an ambivalent experience that provides access to capital while also generating social burdens. Loan funds were used in mixed ways, both productive and consumptive, and repayment was viewed as a moral practice. The quantitative analysis identifies repayment strategy as the strongest predictor of household economic empowerment (β = 0.511, p < .001), whereas fund utilization patterns have a negative effect (β = −0.258, p < .001). Access to formal credit itself is not significant (β = 0.088, p = 0.197). These results indicate that empowerment is shaped more by women’s agency in managing credit, particularly repayment discipline and productive allocation, than by the mere availability of formal credit access.